PENGARUH AKSESIBILITAS DAN DAYA TARIK TERHADAP LOYALITAS WISATA DENGAN AMENITAS SEBAGAI VARIABEL INTERVENING PADA DESTINASI WISATA TUK-TUK SIADONG KABUPATEN SAMOSIR - Silaban, Pantas H.; Silalahi, Andri D. K.; Octoyuda, Edgar; Sinaga, Desi (Jurnal Manajemen dan Bisnis, 2020)
This research aims to analyze the influence of accessibility and destination attraction on tourist loyalty mediated by the destination amenity. The research methodology uses the Structural Equation Modelling (SEM) to analyze the quantitative data were collected accidentally from the respondents in the destination. The sample method uses purposive random sampling with number of sample are 240 respondents. The respondents should meet the following criteria (1) who visit the destination at least 2 times or more, (2) who visit the destination at least in 2018. The results shows that (1) accessibility insignificantly influence the destination amenity, (2) destination attraction significantly influence the destination amenity, (3) accessibility insignificantly influence the tourists loyalty, (4) destination attractions insignificantly influence the tourists loyalty, (5) destination amenity insignificantly influence the tourists loyalty, (6) the destination amenity insignificantly mediated accessibility on tourists loyalty and (7) destination amenity insignificantly mediated the destination attraction on tourists loyalty